Do Meta-Analyses of Intervention/Prevention Programs in the Field of Criminology Meet the Tests of Transparency and Reproducibility?. (July 2023) - Wong, Jennifer S.; Bouchard, Jessica
While assessments of transparent reporting practices in meta-analyses are not uncommon in the field of health sciences interventions, they are limited in the social sciences and to our knowledge are non-existent in criminology. Modified PRISMA 2020 checklists were used to assess transparency and reproducibility of reporting for a sample of 33 meta-analyses of intervention/prevention evaluations published in scholarly journals between 2016 and 2021. Results indicate that the average rate of transparent reporting practices was 63%; adherence varied considerably across studies and subscales, with low rates of adherence for some core checklist items. Overwhelmingly, studies were not reproducible in their entirety; article word count was significantly correlated with reproducibility ( r = 0.4028, p < .03). These findings suggest that substantial changes to reporting practices are necessary to meet traditional meta-analytic claims of transparency and reproducibility. Study limitations include sample size, coding instruments, and coding subjectivity.